The first Monagas administration in Venezuela, 1847-1851 - Castillo, R (1981)
This thesis attempts an impartial enquiry into the events surrounding the power struggle between José Tadeo Monagas and José' Antonio Páez, 1847-1851 . The political, economic, and social aspects of Venezuela at that time are considered. The contribution of Monagas to the country's historical process is then examined: how the country changed during this time, and how Monagas changed it. Chapter I considers Monagas's background and his ascendancy at a local level before and during the War of Independence. Chapter II examines the post-independence period until his election as president, 1829-1847, with particular emphasis on the growth of his prestige at a national level. Monagas's first year in power is covered in chapter III, including discussion of the issues he had to face, and the tensions created with the conservative ruling group. Chapter IV examines the event of 24 January 1848 in depth for a clearer picture of the break between the Conservatives and the Congress they controlled and Monagas and his Liberal supporters. Civil war breaks out in chapter V. Liberal policy and the efforts made by both sides to maintain the struggle are covered in chapter VI. Páez's defeat and exile and Monagas's policies are considered in chapter VII. Chapter VIII shows the consolidation of Monagas's power and his success in having his brother elected to succeed him. Chapter IX argues that Monagas was a clever political and military leader who was able to challenge Páez successfully and to perpetuate his own rule. He presided with some skill over a necessary evolution in Venezuelan politics.